Seminar Kewirausahaan – Success Before 30 Persekutuan Pemuda Gereja Toraja (PPGT) Klasis Nonongan Salu - Grace Sriati Mengga; Wanie Bandaso; Agustinus Mantong; Althon K Pongtuluran; Dian Intan Tangkeallo (Universitas Kristen Indonesia Toraja, 2023)
This community service aims to provide comprehensive education about trichiasis, a condition in which eyelashes grow into the eye as well as provide an explanation of the definition, causes, symptoms, and risks associated with trichiasis and eye health. This counseling also provides education on various available treatment methods, ranging from medical treatment and prevention that can be taken to keep the eyes healthy. The form of community service is counseling using the media in the form of powerpoint slides and brochures accompanied by pre-test and post-test to assess the level of public knowledge. information about trichiasis. The level of knowledge before counseling regarding trichiasis and eye health was obtained by all respondents who were still lacking and after counseling there was an increase in the level of knowledge of respondents as much as 89% with a good level of knowledge.